“Tell me a story, dear, that is not true”: Love, Historicity, and Transience in A. Mary F. Robinson’s An Italian Garden - Rigg, Patricia Diane (Australasian Journal of Victorian Studies, 2013)
In this essay, I suggest that Robinson shifted from the aestheticist socialism of The New Arcadia to aestheticist individualism popularized by Herbert Spencer and Samuel Smiles in the 1880s. An Italian Garden reflects Robinson’s intimacy with Vernon Lee, the unique liaison between the women informing the nature of love depicted in the volume. Therefore, I read An Italian Garden in the context of Robinson’s interest in Italy, in Italian poetic forms, and in Vernon Lee, interests which inform her poetic depiction of love developed within the framework of an androgynous, aestheticist, and individualistic form of human experience. Robinson poeticizes and aestheticizes conflicted feelings about love, desire, and death that blur gender boundaries and gendered expectations.